Določitev mutacij v eksonu 12 gena JAK2 pri bolnikih s pravo policitemijo - Mandelc, Marija-Jedrt (Zdravniški vestnik, 2012)
Background: Polycythemia vera (PV) is characterized by erythrocytosis and mutation in JAK2 gene. More than 95 % of patients with PV have somatic mutation JAK2 V617F. Recently, severalnovel JAK2 exon 12 mutations in PV patients and unmutated JAK2 V617F were found. The aim of the study was to introduce methods for the detection of JAK2 exon 12 mutations in patients withPV or unclear erythrocytosis and with unmutated JAK2 V617F. Methods: Six patients with an increased red cell mass determined by Complete Blood Count (CBC) test and with unmutated JAK2 V617F were included in the study. Granulocytes were isolated from peripheral blood or bone marrow aspirates by Ficoll density centrifugation followed by erythrocytes lysis. Total cellular RNA was isolated from cells and used to prepare complementary DNA (cDNA) by reverse transcription. Detection of JAK2 exon 12 mutation was performed by quantitative real time PCR and by melting curve analyses using dual hybridization probes, by classical PCR and agarose gel electrophoresis. The type of mutation was determined by direct sequencing of the classical PCR products. Results: We detected JAK2 exon 12 mutation in two out of six patients. We determined the deletion p.Asn542_Glu543del in one patient and thedeletion p.Glu543_Asp544del in another one. The mutations have been alreadydescribed. Conclusions: In two out of six patients we detected JAK2 exon 12 mutation and confirmed the diagnosis of PV. We conclude that JAK2 exon12 mutation analysis by the methods used contributes to the diagnosis of PV or erythrocytosis in patients with unmutated JAK2 V617F mutation.
Keywords: diagnostika; eritrocitoza; erythrocytosis; hematologija; JAK2 exon 12; JAK2 V617F; mutacije; polycythrocytosis; prava policitemija